ACEHNESE MORPHOLOGICAL INTERFERENCE IN INDONESIAN LANGUAGE USAGE OF BUMI PERSADA UNIVERSITY STUDENTS - Azhari; Sitti Aminah; Helmiyadi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Indonesian has a role as the national language as well as the official language of the country, so it needs to be fostered and developed as a standard language. However, this development effort is often hampered by interference or deviation caused by the influence of regional languages, which is still strong in Indonesian society. Even among students, who are supposed to write scientific papers according to official languae rgules, language interference still occurs. This condition can hinder effective communication and should no longer be found in students. This research uses a qualitative approach with a descriptive method to describe the phenomenon under study systematically, factually, and accurately. Data were collected through observation with the help of written texts in the form of free essays. The results showed that there were four forms of Acehnese morphological interference in the writing of Universitas Bumi Persada students who were undergoing teacher practice in Paya Tebang Village. The four words consist of three basic words-Rumoh, Pinto, and mangat-and one repeated word, namely grop-grop. In order to preserve Indonesian as the identity of the nation and the official language of the state, the use of these forms of interference must be avoided. If left unchecked, such interference can undermine the uniformity and accuracy of the Indonesian language in accordance with the applicable rules.